EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE TIPE TSTS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTs AL-AHLIYAH AEK BADAK - Nurdiani Pulungan (JURNAL MathEdu (Mathematic Education Journal), 2018)
Abstract The aims of this study is to: 1) describe of using TSTS (Two Stay Two Stray) learning model, 2) describe students’ mathematic problem solving ability before and after using TSTS learning model, and 3) there is a significant influence of using TSTS learning model on students’ mathematic problem solving ability at the eighth grade students of MTs Al- Ahliyah Aek Badak. This research was conducted by applying experimental method (one group pretest post test design) with sample 27 students and they were taken by using simple total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the score of using TSTS learning model was 3.25 (very good category), b) the average of students’ mathematic problem solving ability before using TSTS learning model was 43.51 (poor category) and after using TSTS learning model was 77.71 (good category). Furthermore, by using paired sample ttest and helping SPSS version 17, the result showed the significant value was less than 0.05 (0.000<0.05). It TSTS ns, there is a significant influence of using TSTS learning model on students’ mathematic problem solving ability at the eighth grade students of MTs Al- Ahliyah Aek Badak. Keywords: TSTS learning model, mathematic problem solving ability